Cataract couching and the goat's eye. Issue 7 (26th September 2018) - Leffler, Christopher T.; Schwartz, Stephen G.; Peterson, Eric; Busscher, Joshua
Abstract: At the start of the third century, a story told by Claudius Aelianus, Leonidas of Alexandria and pseudo‐Galen held that couching originated when a goat with cataract punctured its eye with a thorn. The significance of this story is unknown. We reviewed Graeco‐Roman texts to identify the relevance of the goat to the eye. In the works of Hippocrates, Aristotle and Galen, the goat's eye was an eye with intermediate brightness or colour. A dark brown eye with a black pupil was healthy and required no treatment. A bright glaukos eye, with extensive corneal edema or scarring, was not amenable to couching. An eye with a white cataract behind an undilated pupil would appear to have an intermediate brightness and was potentially amenable to couching. The origin myth probably arose when an instructor explained that couching works best for a goat's eye, that is, an eye with intermediate brightness.